Penerapan Model Small Group Discussion dalam Pembejaran Menulis Paragraf Argumentasi - Frieska Maryova; Rohana, Rohana (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
: This research contains how to apply the small group discussion model in learning to write argumentative paragraphs. Judging from the needs of teachers and students in achieving learning objectives, this learning method is considered effective, so this research is a solution offered in learning to write argumentative paragraphs using the small group discussion learning model. This research uses a qualitative descriptive method because the method or technique for collecting data and analyzing data in this research uses word or sentence descriptions from the results of the simple formulas presented. Using data collection techniques, it is then analyzed to produce conclusions that have a positive impact on students and teachers. The results obtained in this study show that the average score obtained was 78.16, which is in the good category. A total of 38 students or out of the total number of students, 8 students or 21.05% scored in the very good category. A total of 30 students or 78.94% obtained scores in the range 75-89 in the good category. It can be concluded that this research is very useful for teachers and students in applying the small group discussion learning model for learning argumentative paragraphs.